Implantación de un sistema contable en la empresa SC-CAD Jorge Vinicio Sánchez Pastor en la ciudad de Lago Agrio, Provincia de Sucumbíos correspondiente al periodo del 01 de enero al 31 de marzo del 2016 - Chinche López, Carlos Julio (2018)
The present thesis work was carried out with the purpose of Implementing an Accounting System in the SC-CAD Company Jorge Vinicio Sánchez, where favorable results will be obtained to improve the economic activity and allow the owner to make the appropriate decisions; also complying with some of the requirements necessary to qualify for the degree in Accounting and Audit Engineering according to what is established by the Regulations of Academic Regime of the National University of Loja. The specific objectives were met, using the methods and techniques proposed, starting from the collection of information, preparing the Plan and Manual of Accounts, according to the needs of the company, records such as the Inventory, Initial Situation Status , Auxiliary Books, Daily Book, General Ledger, Verification Balance Sheet, Worksheet, Financial Situation Statements and Cash Flow, the management was measured through Financial Analysis of Liquidity, Indebtedness and Profitability, where the real economic status could be determined , allowing the owner to provide reliable information on Company Accounting. At the end, it is concluded that the SC-CAD Company Jorge Vinicio Sánchez has obtained loss within its economic activity, with outstanding balances of the workers and the Ecuadorian Institute of Social Security IESS, during the accounting period it is reflected that the expenses exceed to income, for which consideration is given to the respective conclusions and recommendations that are alternatives to control and improve economic activity.